Music Composition Kaliyuga | Komposisi Musik Kaliyuga - Kadek Guntriana; Garwa I Ketut (GHURNITA: Jurnal Seni Karawitan, 2023)
Kaliyuga is one of the most recent eras among other Yugas in a cycle of development of the Hindu Religion era in Bali, which is known as Catur Yuga. Kaliyuga is called the Age of Darkness or also known as the Age of Desolation. This creation of percussion is inspired by the negative side of human nature in the Kaliyuga era, in which the human body was filled and controlled by the nature of Adharma. The creator created a creation of percussion work entitled "Kaliyuga" by using the media said barungan gamelan Gong Kebyar. The creator has an interest in transforming it into a new creation percussion work, which uses the creation method of Alma M. Hawkins to be able to realize this work. There are three important stages that must be passed from the method, namely the assessment/exploration stage, the trial/improvisation stage, and the forming/forming stage. This method is used by the creators as a reference or basis in creating this percussion work. The benefit of the creation of this work is that the creator can add to his work experience and this work was created for the purpose of being the author's Final Project Work in his undergraduate study program at the Indonesian Art Institute in Denpasar.